PP35. NEUTROPHIL LYMPHOCYTE COUNT RATIO (NLCR) IN PREDICTING THE HISTOLOGICAL GRADE OF PAEDIATRIC CNS TUMOURS - Saeed, Dr Fozia (Neuro Oncol, 2017)
Neutrophil lymphocyte count ratio (NLCR) in predicting the histological grade of paediatric CNS tumours INTRODUCTION: Neutrophil Lymphocyte Count Ratio (NLCR) is an established prognostic marker for renal, lung and colorectal carcinomas, and has been suggested to be predictive of histological grade in adult intrinsic primary brain tumours. The purpose of this study was to determine the prognostic impact of pre-operative NLCR in paediatric CNS tumours, in view of disease specific survival and also the prognostic impact of pre-operative NLCR in paediatric CNS tumours stratified by intrinsic subtypes. METHODS: Retrospective analysis at a single centre. Patients less than 18 years old at the time of surgery who underwent tumour-related procedures from 2006–2015. Craniopharyngiomas, recurrent tumours, previous bone marrow transplants and metastases were excluded. Pre-operative NLCRs (collected before the diagnosis of intracranial pathology, and before administration of steroids) were matched with histological diagnosis for each patient. Post-operative NLCR was also recorded where possible. RESULTS: A total of 112 paediatric patients (71 males and 41 females) of an average age 8 ± 4 years, with a diagnosis of primary intrinsic CNS tumours had pre-operative NLCR that could be matched to final histological grade. WHO Grade 1 and 2 tumours (‘low grade’, n=53) had a mean NLCR of 2.42 (95% CI 1.81–3.02) compared to a mean NLCR of 3.56 (95% CI 2.73–4.79) for Grade 3 and 4 tumours (‘high grade’, n=59), which was statistically significant (p=0.035). One-way ANOVA showed a statistically significant variance for NLCR between each grade of tumour. The NLCR for Medulloblastoma was significantly higher (4.2) compared to the low grade cohort (2.42) which was statistically significant (p=0.006). Further analysis of the medullobalstomas showed NLCR for metastatic (n=8, 5.15) and non-metastatic (n=16, 4.9) tumours to have no difference between them (p=0.56). CONCLUSION: Our preliminary results are consistent with published literature on adult tumours and suggest that a larger pre-operative NLCR may correlate with a higher final histological grade in paediatric CNS tumours. Sub-group analysis showed that both metastatic and non-metastatic medulloblastomas have a significantly higher NLCR than low grade CNS tumours.